Effects of olives and their constituents on the expression of ulcerative colitis: a systematic review of randomised controlled trials. Issue 8 (28th April 2022) - Daniel, Kenneth; Vitetta, Luis; Fiatarone Singh, Maria A.
Abstract: Extra virgin olive oil is often associated with anti-inflammatory and antioxidant properties. Its effects on inflammatory conditions such as ulcerative colitis (UC), however, have yet to be defined. As such, we aimed to conduct a systematic review and meta-analysis of studies investigating olive-based interventions in UC. A comprehensive database search for randomised controlled trials was performed between 9 July 2018 and 16 August 2018. Studies identified from search alerts were included up to 22 June 2020. Both individuals living with UC at any disease stage and murine models of UC were included in this review. No human trials meeting the eligibility criteria were identified, while nineteen animal studies comprised 849 murine models of UC were included in this review. Pooling of the data could not be performed due to heterogeneous outcomes; however, general trends favouring olive-based interventions were identified. Milder disease expression including weight maintenance, reduced rectal bleeding and well-formed stools favouring olive-based interventions was statistically significant in 16/19 studies, with moderate-to-large effect sizes (−0·66 (95 % CI −1·56, 0·24) to −12·70 (95 % CI −16·8, −8·7)). Olive-based interventions did not prevent the development of colitis-like pathologies in any study. In conclusion, effects of olive-based interventions on murine models of UC appear promising, with milder disease outcomes favouring the intervention in most trials and effect sizes suggesting potential clinical relevance. However, the lack of published randomised controlled human trials warrants further investigation to determine if these effects would translate to individuals living with UC.